New names of Ilex and Ilexpollenites (Aquifoliaceae), extant and fossil: Addendum Notulae Systematicae ad Palaeofloram Europaeam spectantes II. Aquifoliaceae - Doweld, Alexander B. (Phytotaxa, 2022)
N/A